Validation of a rapid remote digital test for impaired cognition using clinical dementia rating and mini-mental state examination: An observational research study - Alim-Marvasti, Ali; Kuleindiren, Narayan; Harvey, Kirsten; Ciocca, Matteo; Lin, Aaron; Selim, Hamzah; Mahmud, Mohammad (Frontiers in Digital Health, 2022)
Background The Clinical Dementia Rating (CDR) and Mini-Mental State Examination (MMSE) are useful screening tools for mild cognitive impairment (MCI). However, these tests require qualified in-person supervision and take up to 60 or 15 minutes to complete, respectively. We developed a digital cognitive screening test (M-CogScore) that can be completed remotely in under 5 minutes without supervision. We set out to validate M-CogScore in head-to-head comparisons with CDR and MMSE. Results 72 participants completed all three tests. The M-CogScore correlated with both MMSE-2 (r=0.66, p<0.0001) and impaired cognition on CDR (Mann Whitney U=187, p<0.001). M-CogScore achieved an AUC of 0.85 (95% bootstrapped CI [0.80, 0.91]), when differentiating between normal and impaired cognition, compared to an AUC of 0.78 [0.72, 0.84] for MMSE-2 (p=0.21) Conclusion M-CogScore was significantly correlated with established cognitive tests, including CDR and MMSE-2. M-CogScore can be taken remotely without supervision, is automatically scored, has less of a ceiling effect than the MMSE-2, and takes significantly less time to complete. Digital screening tests such as M-CogScore are desirable to aid in rapid and remote clinical cognitive evaluations.